Safety Evaluation of Chicken Satay In Yogyakarta Indonesia Based on Benzo[A]Pyrene Content - Irnanda, Khairunissa; Meiftasari, Argandita; Nagadi, Standie; Lukitaningsih, Endang (Indonesian Research Gateway, 2012)
Chicken satay is one of Indonesian food which is very popular and processed by direct flame over the meat. But, almost every types of food which are prepared by direct flame will produce chemical compounds that contributes to the incidence of cancer. Polycyclic aromatic hydrocarbons (PAH) is a group of compound which can cause cancer and is resulted from the incomplete combustion of fossil fuels or pyrolysis of organic material containing carbon and hydrogen atoms. One PAH compound having mutagenic and highly carcinogenic effect is benzo[a]pyrene which is the highest content found in foods that are burned directly on the flame. This study aims to establish levels of benzo[a]pyrene contained in chicken satay in Yogyakarta, Indonesia and to evaluate how it meets with the maximumbenzo[a]pyrene limit in the burned food based on National Agency of Drug and Food Control which is equal to 5 ppb (5 mg/kg). Analysis were performed by Gas Chromatography method using helium as carrier gas and CPCB-Sil8 as stationary phase. After the sample was prepared and analysed by GC, it is known that the amount of benzo[a]pyrene in chicken satay found in Yogyakarta are ranging from 2.5 to 393.32 ppb. The result are quite high and far above the safety limit determined by National Agency of Drug and Food Control.Therefore, the result of the research needs to be socialized to the public so that people can be more aware about the danger of food they consume.Keywords: chicken satay, benzo[a]pyrene (BaP), policyclic aromatic hidrocarbon (PAH), carsinogen, Yogyakarta